Parapharengeal Unicentric Castleman Disease With Nephrotic Syndrome (Iranian Journal of Kidney Diseases, 2013)
Castleman disease (CD) is a rare lymphoproliferative disorder, first described in 1956. This case report describes a 27-year-old man with hyaline vascular unicentric CD, first presented with edema and hypertension. On initial evaluation for edema, 24-hour urine collection revealed 8200 mg/24 h protein excretion. Pathologic examination of the kidney specimen showed diffuse mesangial lesions with segmental subepithelial deposition. On follow-up for nephrotic syndrome, the patient experienced a feeling of a mass in his pharynx and deterioration of previous snoring, documented by neck magnetic resonance imaging. Pathology report of the excisional biopsy showed CD. Treatment with corticosteroids and partial excision can be considered as an alternative to surgery for unresectable unicentric CD. The 5-year follow-up showed that this strategy could lead to remission.